Pengaruh Profitabilitas, Solvabilitas Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Intervening - Ajeng Kasiatin Ningsih; Hari Setiono; M. Bahril Imiddaviq (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study examines the impact of profitability and solvency on firm value, with firm size as an intervening variable, in food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2020 to 2024. This research is driven by inconsistent results from previous studies and the dynamic conditions faced by this sector in the post-pandemic era. A quantitative associative method was used with purposive sampling, resulting in 29 companies as research samples and 145 observations. Data were analyzed using multiple linear regression and path analysis with IBM SPSS 2022. Return on equity (ROE) measures profitability, debt-to-equity ratio (DER) measures solvency, price-to-book value (PBV) measures firm value, and total assets (Ln) measures firm size. The findings show that profitability and solvency significantly affect firm size. Profitability and firm size significantly affect firm value, while solvency shows no direct impact on firm value. However, both profitability and solvency indirectly affect firm value through firm size. These results show how important firm size is in linking financial ratios and provide concrete evidence supporting signaling theory to explain how investors view the food and beverage industry in Indonesia.